Altered self-reactive antibody repertoires are a general feature of patients with myelodysplastic syndrome - Stahl, Dorothea; Egerer, Gerlinde; Goldschmidt, Hartmut; Sibrowski, Walter; Kazatchkine, Michel D.; Kaveri, Srini V. (Journal of autoimmunity, 2001)
Myelodysplastic syndrome (MDS) is characterized by an acquired clonal disorder of haematopoietic progenitor cells that results in inhibition of normal haematopoiesis and contributes to the development of haematological malignancies. Autoimmune syndromes may occur in MDS, but they are not a major clinical feature of the disease. In the present study, we have analysed the global antibody repertoires of IgM and IgG in plasma of 10 patients with MDS toward self- and non-self-antigens by quantitative immunoblotting. Myelodysplastic syndrome patients included in this study did not exhibit autoimmune symptoms nor secondary haematological neoplastic disease. Data were compared by means of multiparametric statistical analysis. We demonstrate that the antibody repertoires of self-reactive IgM and IgG of patients with MDS exhibit significantly altered patterns of reactivity, as compared to those of healthy individuals. In contrast, reactivity patterns of IgM in plasma of patients and of healthy controls toward non-self-antigens were similar, whereas reactivity patterns of IgG of patients and healthy subjects toward non-self-antigens were discriminated by multiparametric statistical analysis. These observations indicate that a broad disturbance of self-recognition mechanisms is a general feature of patients with MDS. A failure in the regulation of self-reactivity may contribute to the pathogenesis of MDS.